Advances in nutritional metabolic therapy to impede the progression of critical illness - Chen, Wenwei; Song, Jia; Gong, Shijin (Frontiers in Nutrition, 2024)
【Abstract】 With the advancement of medical care and the continuous improvement of organ support technologies, some critically ill patients survive the acute phase of their illness but still experience persistent organ dysfunction, necessitating long-term reliance on intensive care and organ support, known as chronic critical illness. Chronic critical illness is characterized by prolonged hospital stays, high mortality rates, and significant resource consumption. Patients with chronic critical illness often suffer from malnutrition, compromised immune function, and poor baseline health, which, combined with factors like shock or trauma, can lead to intestinal mucosal damage. Therefore, effective nutritional intervention for patients with chronic critical illness remains a key research focus. Nutritional therapy has emerged as one of the essential components of the overall treatment strategy for chronic critical illness. This paper aims to provide a comprehensive review of the latest research progress in nutritional support therapy for patients with chronic critical illness. 【Keywords】 chronic critical illness; nutrition support; reviewThe term Chronic Critical Illness (CCI) was first introduced by Girard [1] in 1985 to describe a group of patients who have survived the acute phase of their illness but continue to experience persistent organ dysfunction, necessitating prolonged reliance on intensive care and organ support [2] . This condition is an inevitable outcome of modern medical advancement. With the progress in healthcare standards and the exacerbation of population aging, the prevalence of CCI is on the rise globally, particularly in high-income countries [3] , garnering significant attention in the academic community.Previously, CCI has been described using various terms such as critical illness polyneuropathy, critical illness myopathy, ICU-acquired weakness, and post-intensive care